Pengaruh Kepemimpinan Terhadap Meningkatnya Orientasi Pembelajaran dan Kreativitas Guru - Ririn Handayani; Helwen Heri (Kafa`ah: Journal of Gender Studies, 2019)
The  principals competency and their ability in motivating the teacher as well making them creative are very crucial to meet school success. This study will look at which leadership styles are more suitable to be practiced in educational organizations, whether transformational or transactional leadership in improving teacher learning and creativity orientation. This research will also use gender as a moderator. This study uses quantitative methods with a population of 1,602 people from 56 High Schools in Pekanbaru. Sampling using stratified random sampling. Calculation of the number with N (population) = 1.602 then n (sample) = 310. Analyzer used is multiple linear regression. Findings: It has been found that transformational and transactional leadership influences the increasing orientation of teacher learning and creativity. But it has also been found that transformational leadership is greater in influencing the increasing orientation of teacher learning and creativity. That women is better than to headmaster than male.